1, 4, 5, 6-Tetrahydro-2-methyl-4-pyrimidinecarboxylic acid (THMP) – A novel universal stress protein data from Halomonas species for pharmaceutical applications - Bhagwan Narayan Rekadwad (Data in Brief, 2024)
Genomes of Halomonas species have been studied using the BV-BRC Bioinformatics tool for the presence of CDS, non-CDS, AMR genes, VF genes, transporters, drug targets, GC content, and GC skew from outside to the center of the circular view, followed by phylogenetic analysis of unique 1, 4, 5, 6-Tetrahydro-2-methyl-4-pyrimidinecarboxylic acid (THMP) gene clusters for relatedness within the genus Halomonas. Protein structure and chemical structure of 1, 4, 5, 6-Tetrahydro-2-methyl-4-pyrimidinecarboxylic acid (THMP) encoded by the UspA gene in Halomonas strains and amino acid sequence of the novel UspA gene have been predicted by computational method.